RANCANG BANGUN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA TERHUBUNG DENGAN JARINGAN LISTRIK PLN PADA KANTOR DI BINTARO - JAKARTA SELATAN - Brilliant Brilliant; Robinson Purba; Atmonobudi Soebagio (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2019)
This paper discusses the design and construction of a solar powered generation system (PVs) in a 3-storey office building in the Bintaro area. The paper discusses the costs to build PVs, as well as an analysis of the value of investments using RETScreen Expert software. The calculation to get the PVs capacity is based on the area of ​​the roof and the electricity load of the office. This PV system will be integrated with the PLN electricity network in serving electricity loads in offices on each floor. The type of PV module has 305Wp capacity per module. The investment value is simulated with the assumption that battery units are replacemed every 3 years, repayment of the loan for 10 years with an advance of 50%, an interest rate of 5.75% and inflation of 3.28%. From the simulation we also obtained a comparison of investments between replacing the battery units once every 3 years with every 10 years, which became the basis for the decision of the PLTS owner to determine the scheme to be choiced.